Dukungan Sosial dan Kecerdasan Emosi dengan Resiliensi Korban Banjir - Anwaruddin, Hoirul (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract This study aims to determine the correlation between social support and emotional intelligence with resilience to flood victims. Retrieval of data in this study uses a scale of resilience, scale of support, and emotional intelligence distributed to 100 research subjects, namely flood victims in Dalpenang Sampang village using purposive sampling technique. The results of the analysis of research data using multiple regression analysis shows that there is a positive relationship between social support and emotional intelligence with resilience which is shown by the F number regression = 103.783 with p = 0.000 (p <0.001). Variables of social support and emotional intelligence simultaneously and very significantly correlate with resilience. Partially found the value of t regression between social support and resilience = 10.410, and partial r = 0.726, p = 0.00 (p <0.05), this means there is a positive and significant relationship between social support and resilience. The partial test also found t regression between emotional intelligence and resilience = 3.675 and r partial = 0.350 (p <0.05), this means there is a positive and very significant relationship between emotional intelligence and resilience. These results indicate that the three proposed hypotheses are accepted. Keywords: social support, emotional intelligence, resilience